Comparative Study of the Application of the 'Conseil d'État' Concept in State Administrative Courts in Indonesia - Azam, Muhammad Adzkiya; Mamonto, Moch. Andry Wikra Wardhana; Hidayat, Arif; Yudhanti, Ristina (Indonesian State Law Review, 2024)
The State Administrative Court (PTUN) in Indonesia plays a crucial role in resolving disputes between individuals or legal entities and state administrative bodies or officials, serving as a protector of justice in the relationship between government and society. Similarly, France's Conseil d'État, established in 1799, serves as the highest administrative judicial body, resolving conflicts between citizens and the government, while also advising the government on legislative matters. This article presents a comparative study of the application of the Conseil d'État concept in the context of Indonesia’s State Administrative Courts. Using a normative juridical research method, the study examines whether the structures, functions, and practices of the Conseil d'État can be adapted to enhance the Indonesian legal system. The research explores key differences and similarities in the roles of these institutions, focusing on procedural, institutional, and advisory aspects. The findings suggest that while both institutions share a common goal of ensuring accountability and fairness in state administration, the application of the Conseil d'État model in Indonesia may face challenges due to differences in legal traditions, governance structures, and administrative practices. Nevertheless, adopting certain aspects of the Conseil d'État, such as its advisory role and specialized procedural mechanisms, could improve the efficiency and authority of the PTUN. This research contributes to the ongoing discourse on legal reforms in Indonesia’s administrative justice system, offering valuable insights into potential reforms that could enhance judicial independence and promote better governance. The study's novelty lies in its focus on cross-national legal comparisons, offering a fresh perspective on the adaptation of foreign legal models in Indonesia. Given the urgent need for judicial reform in Indonesia, the findings of this study could guide future policy changes aimed at strengthening administrative justice.